Gender discrimination and perceived fairness in the promotion process of hotel employees. Issue 1 (22nd December 2020) - Russen, Michelle; Dawson, Mary; Madera, Juan M.
Abstract : Purpose: The purpose of this study is to examine hotel managers' perspectives on the promotion process of hotel employees based on the promoted employee's gender, their perceived organizational justice and perceived gender discrimination against women. The moderating role of anti-male bias beliefs in the promotion process was examined. Design/methodology/approach: The study adopted an experimental design (female vs male promoted) with a sample of 87 hotel managers. Data were analyzed using mediation and moderated mediation analyses. Findings: The results indicated procedural and distributed justice mediates the effect of gender of the promoted employee on perceived gender discrimination against women. It was found that perceptions of anti-male bias moderate the relationship between gender of the promoted employee and distributed justice, demonstrating higher levels of perceived fairness within the organization when a female is promoted, especially when low levels of anti-male bias exist. Practical implications: Many organizations may refrain from offering more promotional opportunities to women for fear of reverse discrimination. This research demonstrates that the organization will be perceived as fairer if it offers more opportunities to women, should create a stronger organizational culture and higher financial performance. Originality/value: To the best of the authors' knowledge, this paper is the first to address the gender inequity in promotional opportunities of hotel employees and demonstrate the overall benefit of combating such inequality. This is the first time that anti-male bias has been addressed in the hospitality context, suggesting the need for more research on reverse discrimination, especially in promotional situations.